STRATEGIES FOR IMPROVING PUBLIC SERVICE PERFORMANCE AT THE NORTH SUNGKAI SUBDISTRICT OFFICE, NORTH LAMPUNG REGENCY - Sherly Erlina; Agus Wahyudi (International Journal of Multidisciplinary Reseach, 2026)
This study examines public service performance, identifies the internal and external factors that influence it, and formulates improvement strategies at the North Sungkai Subdistrict Office, North Lampung Regency. A qualitative descriptive approach supported by quantitative data was employed. Data were collected through observation, in-depth interviews, documentation, and questionnaires. Seven informants were selected purposively, while all 23 personnel, comprising 17 civil servants and 6 government employees under work agreements, were included through a census. The data were analyzed using the Miles, Huberman, and Saldaña model, descriptive analysis, and a SWOT matrix. The findings indicate that productivity, service quality, responsibility, and accountability were good, whereas responsiveness was fairly good and still required faster service delivery and stronger coordination. Organizational strengths included personnel experience, commitment to service, coordination, leadership support, and a clear division of duties. Weaknesses included limited staffing, facilities, training opportunities, and technology utilization. Priority strategies include competency development, service digitalization, facility improvement, strengthening a culture of service excellence, transparency, accountability, continuous service innovation, and periodic performance evaluation, supported consistently and sustainably by the local government.